2015
DOI: 10.3390/pathogens4040708
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Inhibitors that Increase the Sensitivity of Methicillin Resistant Staphylococcus aureus to β-Lactam Antibiotics

Abstract: Staphylococcus aureus are Gram-positive bacteria that are the leading cause of recurrent infections in humans that include pneumonia, bacteremia, osteomyelitis, arthritis, endocarditis, and toxic shock syndrome. The emergence of methicillin resistant S. aureus strains (MRSA) has imposed a significant concern in sustained measures of treatment against these infections. Recently, MRSA strains deficient in expression of a serine/threonine kinase (Stk1 or PknB) were described to exhibit increased sensitivity to β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 23 publications
(33 reference statements)
2
34
1
Order By: Relevance
“…S4 ). Consistent with this, three recent papers have identified small molecule inhibitors of Stk1 that are structurally distinct from the IPAs we identified as PrkA inhibitors ( 41 43 ). These data suggest that GSK690693 selectively inhibits the kinase activity of PrkA relative to Stk1 and highlight the possibility of designing non-broad spectrum, pathogen-specific inhibitors.…”
Section: Resultssupporting
confidence: 81%
“…S4 ). Consistent with this, three recent papers have identified small molecule inhibitors of Stk1 that are structurally distinct from the IPAs we identified as PrkA inhibitors ( 41 43 ). These data suggest that GSK690693 selectively inhibits the kinase activity of PrkA relative to Stk1 and highlight the possibility of designing non-broad spectrum, pathogen-specific inhibitors.…”
Section: Resultssupporting
confidence: 81%
“…Intriguingly, and consistent with the known role of PknB in cell wall homeostasis, these inhibitors were able to significantly potentiate the effect of b-lactams in several types of mycobacteria and in the related Nocardia asteroides [236]. This synergistic concept has also been reported for kinase inhibitors of the nonessential L. monocytogenes PrkA and S. aureus Stk1 Hanks kinases [219,223,[237][238][239][240]. In L. monocytogenes, the broad-spectrum kinase inhibitor staurosporine, as well as some more selective repurposed human kinase inhibitors, was seen to inhibit PrkA activity and sensitize cells to b-lactam drugs [219,237].…”
Section: Drugging Bacterial Kinasessupporting
confidence: 78%
“…In L. monocytogenes, the broad-spectrum kinase inhibitor staurosporine, as well as some more selective repurposed human kinase inhibitors, was seen to inhibit PrkA activity and sensitize cells to b-lactam drugs [219,237]. Similarly, several studies have identified Stk1-inhibiting molecules from small-molecule libraries that sensitize MRSA S. aureus strains to b-lactams [223,[238][239][240]. Notably, Kant et al optimized a quinazoline-based Stk1-inhibiting molecule (Inh2-B1) that potentiates the bactericidal activity of the cephalosporins ceftriaxone and cefotaxime on drug-resistant S. aureus, both in vitro and in an in vivo septicemia mouse model with negligible cytotoxic side effects [240].…”
Section: Drugging Bacterial Kinasesmentioning
confidence: 99%
“…While combination therapy is traditionally used for mycobacterial infections, the limited microbiologic activity of previously optimized PknB inhibitors in combination with traditional first line drugs such as isoniazid and ethambutol did not show any potentiation of activity (Lougheed et al, 2011). Previous data from our lab and others demonstrated that genetic deletion or pharmacologic inhibition of PASTA kinases in Listeria monocytogenes and S. aureus increases susceptibility to β-lactams(Pensinger et al, 2014, Vornhagen et al, 2015). Despite β-lactams' general ineffectiveness against mycobacteria (Sotgiu et al, 2016) our decision to pair IPAs with β-lactams based on our previous data in firmicutes demonstrated significant benefit (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Despite a clear rationale for PknB inhibitors, compounds with biochemical activity thus far have demonstrated poor microbiologic activity (Chapman, Bouloc et al, 2012, Lougheed, Osborne et al, 2011, Naqvi, Malasoni et al, 2014. Pharmacologic inhibition or genetic deletion of PASTA kinases in Listeria monocytogenes and MRSA sensitizes these bacteria to β-lactam antibiotics, suggesting this strategy may be useful in other pathogenic PASTA-kinase containing bacteria (Pensinger, Aliota et al, 2014, Vornhagen, Burnside et al, 2015.…”
Section: Introductionmentioning
confidence: 99%